PEMBERDAYAAN DAN PENINGKATAN KAPASITAS KELEMBAGAAN MASYARAKAT DESA MELALUI AGROWISATA BERBAHASA INGGRIS - Nugraha, Novanda Alim Setya; Khomsah, Siti; Ramadhani, Rima Dias; Laksana, Tri Ginanjar (Devote: Jurnal Pengabdian Masyarakat Global, 2022)
Agribusiness utilizes inorganic waste that can be recycled to produce selling points such as basket bags from plastic waste and dolls from cloth waste. There is a superior product in this business unit, namely processed Jenitri seeds which are processed into handicrafts. Jenitri seeds are not only used as an ornamental tool. In certain beliefs, the work of Jenitri seeds is used as a worship tool and a medical device. Therefore, Jenitri seeds have a fairly high selling value compared to other handicrafts because of their various functions. Adiluhur Tourism Village is a village that is currently under development as a tourist spot with the name Kebumen English Tourism Village (KWIK) and is located in Adiluhur Village, Kec. Adimulyo, Kab. Kebumen. There are 3 business units that are superior and are still in the development stage, namely business units in the fields of tourism (agro-tourism), agriculture (agriculture), and handicrafts (agribusiness). Currently, the primary superior unit in Adiluhur Tourism Village is a business unit in the tourism sector. Agrotourism is managed by CV in collaboration with BUMDes (Village Owned Enterprise) Mulia Jaya. The tour featured in this unit is an introduction to several types of captive animals (various types of snakes, monitor lizards, sea urchins, iguanas, mongooses, Australian geckos, crocodiles, alligator fish, and many more) as well as a museum containing ancient agricultural tools (bronze spoon, harrows, sickles, hoes, nails, antique lamps, and many more). The potential that is being developed in this unit is outbound with the target visitor being Elementary Schools. Not only that, the agro-tourism manager plans to work with the BKSDA (Natural Resources Conservation Center) in caring for the animals in the unit.